“Whenever I think about this, I feel like killing myself, because life has no meaning to me anymore”: an exploration of the consequences of rape victimization for men - Siyabulela Eric Mgolozeli; Sinegugu Evidence Duma (International Journal of Qualitative Studies on Health & Well-Being)
Background and purpose Rape is one of the most common human violations, with devastating consequences for the victims and their families. Although this scourge affects everyone, regardless of gender, studies on rape victimization have largely focused on women and children as the victims. Studies on rape victimization of men are therefore limited and little is known about the consequences of rape victimization for men. Accordingly, this study sought to fill this gap by exploring the consequences of rape victimization for men in the City of Tshwane Metropolitan Municipality, Gauteng Province, South Africa Method A qualitative research approach underpinned by interpretative phenomenological analysis (IPA) was used to collect data from a purposive sample of eleven participants. Data was collected using semi-structured face-to-face individual interviews and analysed using the IPA framework. Trustworthiness and validity of study findings was ensured by following Lincoln and Guba criteria, and the study followed ethical principles outlined in the Declaration of Helsinki on conducting research with human participants. Results Six superordinate themes emerged from the data as consequences of rape victimization for men, namely physical, psychological, emotional, social, spiritual and financial consequences. Conclusion The study provides a comprehensive description of the effects of rape on the overall well-being of men. The findings underscore the need for the development of holistic clinical care management guidelines and psychosocial interventions that are specifically tailored for men post-rape. Furthermore, longitudinal studies on the long-term impact of rape on men should be conducted.